Highlights on Practical Applications of Agents and Multi-Agent Systems International Workshops of PAAMS 2013, Salamanca, Spain, May 22-24, 2013. Proceedings - Corchado, Juan M.; Bajo, Javier; Kozlak, Jaroslaw; Pawlewski, Pawel; Molina, Jose M.; Julian, Vicente; Silveira, Ricardo Azambuja; Unland, Rainer; Giroux, Sylvain; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Workshops which complemented the 11th International Conference on Practical Applications of Agents and Multi-Agent Systems, PAAMS 2013, held in Salamanca, Spain, in May 2013. This volume presents the papers that have been accepted for the workshops: Workshop on Agent-based Approaches for the Transportation Modeling and Optimization, Workshop on Agent-Based Solutions for Manufacturing and Supply Chain, Workshop on User-Centric Technologies and Applications, Workshop on Conflict Resolution in Decision Making, Workshop on Multi-Agent System Based Learning Environments, Workshop on Multi-agent based Applications for Sustainable Energy Systems, Workshop on Agents and multi-agent Systems for AAL and e-Health
Workshop on Agent-based Approaches for the Transportation Modeling and Optimization -- Workshop on Agent-Based Solutions for Manufacturing and Supply Chain -- Workshop on User-Centric Technologies and Applications -- Workshop on Conflict Resolution in Decision Making -- Workshop on Multi-Agent System Based Learning Environments -- Workshop on Multi-agent based Applications for Sustainable Energy Systems -- Workshop on Agents and multi-agent Systems for AAL and e-Health.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Education; Computer Science; Artificial Intelligence (incl. Robotics).; Computers and Education; Computers and Society; Information Storage and Retrieval; Computer Applications